Reliability and validity of the Vietnamese version of the Hamilton D-17 scale - Le-Nguyen-Thuy, Phuong; Nguyen-Dao-Uyen, Trang; Tran-Nguyen-Quynh, Anh; Thai, Truc Thanh; Ngo-Tich, Linh; Do-Van, Dung; Duong-Quy, Sy (Frontiers in Psychiatry, 2023)
Background: This study aimed to evaluate the reliability and validity of the Vietnamese version of the Hamilton D-17 scale. Methods: It was a cross-sectional, descriptive, and analytical study. Results: There were 139 depressed and 44 non-depressed patients participating in this study. The results of the study showed that the full-scale Cronbach alpha coefficient was at good level (0.83), the reliability was stable with the full-scale: ICC (Intraclass Correlation Coefficient) = 0.83. Confirmatory factor analysis with two-tier model consisting of 4 evaluation arrays demonstrated that model matched the data: SRMR (Standardized Root Mean Squared Residual) = 0.066; RMSEA ([Root Mean Square Error of Approximation) (90%Cl) = 0.053 (0.036 – 0.069); CFI (comparative fit index) = 0.93; TLI (Tucker Lewis index) = 0.92. The Hamilton D-17 scale and the Patient Health Questionnaire-9 (PHQ-9) scale had a strong correlation with correlation coefficient r = 0.77 (p < 0.001). The Hamilton D-17 scale had very high accuracy with the area under the ROC curve = 0.93 (0.88 – 0.98). Conclusion: The Vietnamese version of the Hamilton D-17 scale has the high validity and reliability to assess depression among depressed patients in Vietnam.